2018
DOI: 10.1136/jnnp-2018-318107
|View full text |Cite
|
Sign up to set email alerts
|

Early use of donepezil against psychosis and cognitive decline in Parkinson’s disease: a randomised controlled trial for 2 years

Abstract: ObjectivesBrain acetylcholine is decreased even in patients with cognitively preserved Parkinson’s disease (PD). We investigated whether early and long-term use of donepezil prevents psychosis in non-demented PD patients.MethodsA double-blinded, placebo-controlled trial was conducted. A total of 145 non-demented PD patients were randomly assigned to receive 5 mg/day donepezil (n=72) or placebo (n=73) for 96 weeks. Medications for PD were not restricted, but antipsychotic drugs were not permitted throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Forty‐four full‐text articles were retrieved and assessed for eligibility but 25 were excluded due to the behavioral and psychological measure being of a more general nature and not specific to psychosis (n = 11), 15‐25 having no placebo control (n = 10), 26‐35 and having a sample size < 20 (n = 4) 36‐39 . This resulted in 19 trials 40‐58 meeting eligibility for inclusion. Four of these 55‐58 did not report data suitable for inclusion in the quantitative analyses, resulting in 15 trials and 16 datasets (Breier et al 40 reported results from two trials conducted in the United States and Europe) available for meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty‐four full‐text articles were retrieved and assessed for eligibility but 25 were excluded due to the behavioral and psychological measure being of a more general nature and not specific to psychosis (n = 11), 15‐25 having no placebo control (n = 10), 26‐35 and having a sample size < 20 (n = 4) 36‐39 . This resulted in 19 trials 40‐58 meeting eligibility for inclusion. Four of these 55‐58 did not report data suitable for inclusion in the quantitative analyses, resulting in 15 trials and 16 datasets (Breier et al 40 reported results from two trials conducted in the United States and Europe) available for meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in the United States or the United Kingdom/Europe. The mean age of participants was over 70 years of age in all but three trials 46,47,53 . The choice of intervention varied, with most trials using an antipsychotic medication (n = 12) 40,42,43,45‐52,54 or an acetylcholinesterase inhibitor (n = 2) 41,53 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with PD dementia and visual hallucinations had better effects from rivastigmine than those without visual hallucinations [122]. However, a recently published randomized double-blind study that evaluated the early use of another cholinesterase inhibitor, donepezil (5 mg per day), in 145 non-demented PD patients during a two-year period did not prove any prophylactic effect of the drug on development of psychosis in PD [123]. Significant improvements in visual hallucinations during memantine treatment was reported for DLB but not PDD [124,125].…”
Section: Treatmentmentioning
confidence: 99%